Advertising strategy marketing in practice - Wiseman, Peter; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 1991)
This program introduces the concepts of marketing and the techniques available to ultimately sell a product. Firstly, Sandhurst Farm identifies a human need or requirement and a niche market. A target group of consumer, selected and defined in terms of lifestyle image, then guide the development of the marketing strategy for the final product.
Copy available in DVD format
Executive producer, Neil Barrett ; script, Peter Wiseman, Dennis K. Smith
Keywords: Advertising -- Milk -- Australia; Advertising -- Australia